The Relevance of Self-efficacy, Perception, ICT Ability and Teacher Performance (Study on Islamic Teachers in Semarang, Indonesia) - ikhrom, ikhrom (FITK UIN Walisongo, 2020)
The paper aimed to investigate the influence of teacher's self-efficacy and perception on his or her job to performance through ICT ability. The research is a quantitative description using path analysis methods. The population is 1500. They are the Islamic religious teachers in Semarang, Central Java. The researcher used Isaac & Michael's table to determine the number of samples. Based on the table, the samples are 290. The Findings are the teachers’ self-efficacy and perception greatly affect to their performance, while perception is also being the critical factor influences teachers to use ICT in the classroom, but self-efficacy is not the vital thing for teachers' ability to use ICT. The finding recommends that self-efficacy and perception of Islamic teachers are vital aspects of the quality of performance. The use of ICT in the classroom is the critical variable for the quality of teacher performance. AbstrakPenelitian ini bertujuan untuk mengetahui pengaruh self-efficacy dan persepsi guru pada pekerjaannya terhadap kinerja melalui kemampuan TIK. Jenis penelitian ini menggunakan deskriptif kuantitatif dengan metode analisis jalur (path analysis). Populasinya 1500 orang. Mereka adalah para guru Pendidikan Agama Islam di Semarang, Indonesia. Peneliti menggunakan tabel Isaac & Michael untuk menentukan jumlah sampel. Berdasarkan tabel tersebut, sampelnya adalah 290. Temuannya adalah self-efficacy dan persepsi guru sangat berpengaruh terhadap kinerja mereka, sedangkan persepsi juga menjadi faktor kritis yang mempengaruhi guru untuk menggunakan TIK di kelas, tetapi self-efficacy bukan hal yang vital bagi kemampuan guru menggunakan TIK. Temuan ini merekomendasikan bahwa self-efficacy dan persepsi guru Islam merupakan aspek penting dari kualitas kinerja. Penggunaan TIK di kelas merupakan variabel penting untuk kualitas kinerja guru.